Thromboembolic disease in COVID-19 patients: A brief narrative review - Mondal, Samhati (J Intensive Care, 2020)
Corona virus 2 (SARS-CoV2/ Severe Acute Respiratory Syndrome Corona Virus 2) infection has emerged as a global health crisis. Incidence of thromboembolic disease is reported to be high in SARS-CoV2 disease and is seen in a multitude of organ systems ranging from cutaneous thrombosis to pulmonary embolism, stroke or coronary thrombosis sometimes with catastrophic outcomes. Evidence points towards a key role of thromboembolism, hypercoagulability and over production of proinflammatory cytokines mimicking a “cytokine storm” which leads to multiorgan failure. This brief narrative review highlights the pathophysiology and risk factors of thromboembolic disease and provides a framework for management of anticoagulation based on the current evidence.